Efektivitas Program Corporate Social Responsibility BNI Go Green Di Megamendung, Kabupaten Bogor, Jawa Barat - Sri Nadya Nurviani; Dini Gandini Purbaningrum (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
This study aims to find out how the effectiveness of the CSR program that has been implemented by PT BNI (Persero). This study uses Sutrisno's theory (in Antimus 2019) concerning measuring program effectiveness using 5 indicators, namely: Program Understanding, On Target, On Time, Goals Achieved, and Real Change. Data collection techniques used are by way of interviews, documentation and observation. The results of this study indicate that the effectiveness of the CSR program at PT BNI (Persero) cannot be said to be effective because one of the indicators, namely the understanding of the program has not been carried out properly, because PT BNI (Persero)'s strategy in inviting the public to participate in the socialization that is being held is still lacking.,therefore there are still many people who do not understand the meaning of implementing the program, and also because the distance between the organic forest and the community is quite far, so that many people still do not care about the BNI Go-Green Organic Forest CSR program in Megamendung.